Study Comparison of Mathematics Learning Outcomes between the User of Number Head Together (NHT) Learning Models and Conventional Learning - Nur Azizah (Universitas Islam Jember, 2017)
The purpose of the research is to know whether there is difference of mathematics learning result between user of Number Head Together (NHT) learning model with user of conventional learning model and to know what better mathematics learning result between user of learning model Number Head Together (NHT) with user of learning model conventional. The kind of the research is comparative with quantitative approach. The subjects of the research are students of class X1 and X2 at MA Darul Mukhlasin. With the data collecting method that used is documentation, and test. The data analysis method that used is quantitative with t test formula. The result of the research there is difference of mathematics learning result between user of learning model of Number Head Together (NHT) with conventional learning and mathematics learning result of user model of learning Number Head Together (NHT) better than result of learning of mathematic of user of conventional learningKeywords: mathematics learning outcomes, NHT, and conventional learning